2018
DOI: 10.3758/s13414-018-1485-z
|View full text |Cite
|
Sign up to set email alerts
|

Speaker information affects false recognition of unstudied lexical-semantic associates

Abstract: Recognition of and memory for a spoken word can be facilitated by a prior presentation of that word spoken by the same talker. However, it is less clear whether this speaker congruency advantage generalizes to facilitate recognition of unheard related words. The present investigation employed a false memory paradigm to examine whether information about a speaker’s identity in items heard by listeners could influence the recognition of novel items (critical intruders) phonologically or semantically related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…The semantic/associative priming effect was not modulated by speaker match in either of the two studies. Negative findings for lexical indexical effects were also reported by Luthra, Fox, and Blumstein (2018), who examined indexical effects on the false recognition of words.…”
Section: Detecting Effects Of Indexical Information On Semantic Processingmentioning
confidence: 62%
“…The semantic/associative priming effect was not modulated by speaker match in either of the two studies. Negative findings for lexical indexical effects were also reported by Luthra, Fox, and Blumstein (2018), who examined indexical effects on the false recognition of words.…”
Section: Detecting Effects Of Indexical Information On Semantic Processingmentioning
confidence: 62%
“…To maximize the likelihood that listeners would adopt different generative models for the two talkers they heard in the current study, we required listeners to make explicit decisions about talker identity during the initial exposure phasenote that because exposure in this experiment was blocked by talker, listeners simply had to press the same button repeatedly for each exposure phase. However, previous work has suggested that listeners may be more likely to show talker-specific effects when they actively attend to talker identity during encoding of the talkers' voices (Goldinger, 1996;Luthra, Fox, & Blumstein, 2018;Theodore, Blumstein, & Luthra, 2015). Notably, lexically guided perceptual learning has been shown to occur robustly following a variety of exposure tasks (Clarke-Davidson, Luce, & Sawusch, 2008;Drouin & Theodore, 2018;Eisner & McQueen, 2006;Leach & Samuel, 2007;Luthra et al, in press;Maye, Aslin, & Tanenhaus, 2008;McQueen, Norris, & Cutler, 2006;White & Aslin, 2011), though, to our knowledge, no previous studies have used a talker identification task specifically.…”
Section: Experiments 1: Blocked Talker Exposurementioning
confidence: 89%
“…Results of Experiment 2 indicated that feedback did not influence whether talker-specific learning was observed. We had hypothesized that drawing attention to the two talkers might make it easier for listeners to learn each talker's phonetic idiosyncrasies, as previous work has suggested that attention to talker identity at encoding may modulate the strength of talker-specific effects (Goldinger, 1996;Luthra et al, 2018;Theodore et al, 2015). However, the talker identification task used in this study was orthogonal to the phonetic manipulation (i.e., the information that allowed listeners to disentangle whether the ambiguous sound was /s/ or /∫/ came from the lexical signal, not from talker identity), which may explain why no effects of feedback were observed.…”
Section: Discussionmentioning
confidence: 99%
“…non-studied critical lures). Future studies on this topic may directly test this explanation by using word lists that converge on both phonological and semantic critical lures (e.g., see Luthra et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…R (R Core Team, 2016) scripts from Luthra, Fox, and Blumstein (2018; osf.io/5b7ct) were adapted for our purposes, using the glmer function of the lme4 package (Bates, Maechler, Bolker, & Walker, 2015). For further details on the models and scripts, please refer to Luthra et al (2018).…”
Section: Recognitionmentioning
confidence: 99%